1986
DOI: 10.1159/000215353
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Two Regimens of Low Molecular Weight Heparin Fragment (Fragmin) in Preventing Postoperative Venous Thrombolism

Abstract: The efficacy and safety of 2 regimens of Fragmin in preventing postoperative venous thromboembolism was compared on 206 consecutive patients, aged 40 years or more, undergoing major abdominal surgery. Ninety-four patients received a single daily injection of 2,500 U of Fragmin for at least 6 postoperative days (group I), while 112 received 5000 U per day in 2 injections of 2,500 U each (group II). In group I 7.4% of patients and in group II 2.6% of patients developed postoperative deep venous thrombosis (DVT);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…These findings were confirmed by Kakkar et al [ 12] who concluded from another study in patients with abdominal surgery that the application of only 2,500 anti-XaU Fragmin is justified and recommendable.…”
Section: Prophylaxis Of Thromboembolism In General Surgerysupporting
confidence: 63%
“…These findings were confirmed by Kakkar et al [ 12] who concluded from another study in patients with abdominal surgery that the application of only 2,500 anti-XaU Fragmin is justified and recommendable.…”
Section: Prophylaxis Of Thromboembolism In General Surgerysupporting
confidence: 63%
“…The widely used naturally occurring anticoagulant heparin has several side effects such as development of thrombocytopenia [6,7], hemorrhagic effect [8,9], ineffectiveness in congenital or acquired antithrombin deficiencies, and incapacity to inhibit thrombin bound to fibrin [10,11]. It is extracted from pig intestine or bovine lung, posing a risk of zoonoses and potential ethical issues, highlighting a need for alternative anticoagulant and antithrombotic therapies, especially ones that are orally available.…”
Section: Introductionmentioning
confidence: 99%
“…Kabi 2165 and other LM W heparins have been shown to be effective and safe prepara tions for the prophylaxis of DVT in several groups of immobilized patients when used in doses according to their individual anticoag ulant and bleeding properties [18][19][20][21][22][23]. In general surgical patients (less prone to de velop DVT compared to stroke patients) an effective and safe dose of Kabi 2165 seems to be 2,500 anti-Xa U s.c./24 h [24,25], Turpie et al [26] used LMW heparin ORG10172 in stroke patients to prevent DVT and concluded that treated patients developed less DVT and did not suffer from major bleeding accidents.…”
Section: Discussionmentioning
confidence: 99%